Emergency physician interpretation of head CT in trauma and suspected subarachnoid haemorrhage—is it viable? An audit of current practice. Issue 2 (15th February 2010) - Harding, J; Craig, M; Jakeman, N; Young, R; Jabarin, C; Kendall, J
Abstract : Background and objectives: The number of emergency CT head examinations has increased since the introduction of the National Institute for Health and Clinical Excellence (NICE) head injury guidelines. In addition, government targets and changes to medical training impact on how services are delivered. In this context, emergency physicians may have a role to play in the interpretation of CT head images. We have provided such a service for 10 years and set out to audit our practice to establish whether our service is safe, the nature and clinical impact of any errors and whether a similar model may be applicable elsewhere. Method: Audit of emergency department patients over a 27-week period comparing immediate emergency physician interpretation of unenhanced CT head images for trauma or suspected subarachnoid haemorrhage (SAH) with the subsequent neuroradiology report. The clinical significance of any discordance was assessed. Results: CT head interpretations in 9/442 (2%) of trauma and 1/48 (2.1%) of suspected SAH were discordant requiring a change clinical management had the formal neuroradiology report been available immediately. Specialist advice was sought in a further 77 patients. 1/634 of the total sample came to harm. Conclusion: The majority of CT head imaging scans can be interpreted safely by emergency physicians in trauma and suspected subarachnoid haemorrhage. We believe a safe and viable clinical service is provided and such a model is applicable in other centres.